Music selection behaviors in everyday listening - Krause, Amanda; North, Adrian; Hewitt, Lauren (Routledge, 2014)
Data on everyday music listening obtained via the Experience Sampling Method indicated that selection method was related to liking for and emotional response to the music, attention paid to the music, and perceived consequences of hearing the music. Individual listener’s characteristics (e.g., age and level of engagement with music) were associated with selection behaviors. Negative effects resulted when individuals perceived they did not have control over music selection. In contrast, possessing control led to positive consequences such as enjoyment and motivation. These results indicate that control is an important aspect of one’s everyday music experiences.